Graduation Ceremony 2001 - Part 3
Continuation of the CEU Graduation Ceremony of the class of 2000/2001. The ceremony continues with the conferring of the doctoral degrees and special departmental awards. The commencement speech is then delivered by Bronisław Geremek (Polish social and political historian) who earlier in the ceremony received the “CEU Open Society Prize.” The commencement speech is followed by the moving of the tassels which confers the students the status of graduates. The academic recessional and images from the reception are also included here.